Effect of Parenting Style on Drug and Substance Abuse Among Teenage Youth in Kabale Municipality. - Ainembabazi, Marion (Kabale University, 2024)
The study examined the impact of parenting styles on drug and substance abuse among teenagers in Kabale Municipality. The objectives were to evaluate the relationship between authoritative parenting and substance use, explore the connection between permissive parenting and substance use, and analyze the link between neglectful parenting and substance use among youths in Kabale Municipality. The research was cross-sectional and involved a sample size of 80 respondents drawn from a population of 100, using purposive and simple random sampling techniques. Data collection was carried out using structured questionnaires, and inferential statistics were employed for analysis. The findings revealed moderate levels of authoritative, authoritarian, permissive, and neglectful parenting styles. The study concluded that parenting styles are generally linked to drug and substance abuse, with permissive parenting showing a statistically significant positive relationship with substance use among youths in Kabale Municipality (β = 0.939, p = 0.000). The study emphasized the importance of addressing permissive parenting in designing interventions to curb substance use among youth. It recommended that the Ministry of Health enforce stricter regulations, including potentially banning the sale of psychoactive substances, to reduce accessibility and usage among youths. Additionally, parents were advised to exercise greater control over their children and avoid being excessively permissive, among other suggested measures.